Applying Augmented Reality for History Lessons in Japan - Kobayashi, Riko; Sato, Haruka; Suzuki, Ren; Hussain, Sara; Tariq, Usman (Journal Emerging Technologies in Education, 2025)
Background. The integration of Augmented Reality (AR) into history education holds the potential to enhance student engagement and comprehension by providing immersive, interactive learning experiences. A mixed-methods approach was adopted, combining pre- and post-tests with interviews and focus groups. The findings suggest that AR can serve as a transformative tool in history education, bridging the gap between abstract content and lived experience.Purpose. This study investigated the effectiveness of AR-enhanced history lessons in Japanese high schools. A total of 200 students aged 15–18 participated in a quasi-experimental study, with one group receiving AR-based instruction and a control group continuing traditional methods. Method. Quantitative results showed a 25% improvement in historical knowledge among AR users versus 5% in the control group (p < 0.001). Qualitative feedback indicated higher engagement, improved retention, and greater enthusiasm toward history learning. Result. The findings indicate a significant increase in student engagement and understanding of historical events, with 85% of students reporting improved retention and a deeper understanding of history. Teachers noted a positive shift in students’ enthusiasm for learning history.Conclud. AR technology enhances history education by providing immersive and interactive learning experiences, leading to greater student engagement and better knowledge retention.